The Effect of Tax Accounting, Green Accounting, and Carbon Accounting on Environmental, Social, and Governance Performance: Moderated by Green Intellectual Capital - Meidijati, Meidijati; Augustine, Yvonne (Technium Social Sciences Journal, 2022)
Researchers structured this study to obtain empirical evidence about how the effect of tax accounting (TAC), green accounting (GAC), and carbon accounting (CAC) on environmental, social, and governance (ESG) performance moderated by green intellectual capital (GIC). The financing of ESG activities according to tax accounting, green accounting, and carbon accounting. This study uses primary data obtained from respondents to questionnaire answers representing public companies (listed on the Indonesia Stock Exchange (IDX)). The researcher sent questionnaires via company email or email to officials/employees who meet the requirements as respondents. GIC does not strengthen the TAC effect on ESG and CAC effect on ESG, and GIC strengthens the GAC effect on ESG.